AB0451 Clinical and Serological Features of Sjögren's Syndrome Associated with SSB/LA. (15th July 2016) - Bartel, G.G.; Mayer, M.M.; Velez, S.D.; Zazzetti, F.; Andrea, G.; Daciuk, N.I.; Laborde, H.; Barreira, J.C.
Abstract : Background: Sjögren's syndrome (SS) is an autoimmune disease associated with focal lymphocytic infiltration in the epithelium of exocrine glands, and may develop systemic manifestations in about 80% of the patients. Typical antibodies present in SS are antinuclear antibody (ANA), rheumatoid factor, SSA/Ro and SSB/La. SS classification criteria includes SSA/Ro and SSB/La, and their presence is associated with extra-glandular manifestations. The prevalence of SSA/Ro in SS is 30–70%, and is related to increased frequency of dermatologic symptoms, scleritis and interstitial lung disease. The relationship between SSB/La and clinical manifestations has not been previously well established, though it can be found in 5–50% of SS, and may co-exist with SSA/Ro half of the times. SSB/La is found isolated in a very low percentages of SS. Objectives: To evaluate the correlation between the presence of SSB/La antibody with distinct clinical, demographic and serological characteristics of SS. Methods: Adult patients evaluated in the Rheumatology Section (Buenos Aires British Hospital) who fulfilled American European Consensus Group (AECG) SS criteria were included. Three groups were compared according to the antibodies present: 1. Positive SSA/Ro and negative SSB/La 2. Both positive 3. Negative SSA/Ro and positive SSB/La. Mann-Whitney and Fisher tests were used according to variables; those with p<0.05 were introduced in a multivariable analysis by logistic regression. Results: Among 195 patients with SS, 93.8% (n=183) were female. Mean age was 54.7 years and the mean total disease duration was 68.5 months. We excluded from analysis 16/8.2% patients due to missing data, and 29/14.9% patients that were negative for both antibodies. Two groups were finally compared (Group 3 excluded due to low prevalence, n=3/1.5%): 80/41% patients with positive SSA/Ro and negative SSB/La; and 67/34.3% positive SSA/Ro and SSB/La. In the univariate analysis, positive SSA/Ro and SSB/La was statistically found to be associated with recurrent sialoadenitis and palpable purpura. Serological findings associated with this group included positive rheumatoid factor, hypocomplementemia and hypergammaglobulinemia. Poor prognosis features such as palpable purpura (OR 9.5 IC 95% 1.1–79 p 0.037), recurrent sialoadenitis (OR 3.1 IC 95% 1.2–7.7 p 0.011), hypocomplementemia (OR 3.6 IC 95% 1.4–9.4 P 0.0075) and hypergammaglobulinemia (OR 2.7 IC 95% 1.2–6.1 p 0.01) were also statistically significant in the multivariate analysis. Cryoglobulinemia and leucopenia were not found to be associated in both of the analysis. Conclusions: In our population, the presence of SSB/La in patients with positive SSA/Ro was related to recurrent sialoadenitis, palpable purpura, hypocomplementemia, hypergammaglobulinemia and reumathoid factor. Although previous studies are contradictory, our study might justify the systematic search of this antibody due to its clinical relevance and link to poor prognosis factors in SS. Disclosure of Interest: None declared